Scale effects in physical hydraulic engineering models - Heller, Valentin (Journal of hydraulic research, 2011)
Scale effects arise due to force ratios which are not identical between a model and its real-world prototype and result in deviations between the up-scaled model and prototype observations. This review article considers mechanical, Froude and Reynolds model-prototype similarities, describes scale effects for typical hydraulic flow phenomena and discusses how scale effects are avoided, compensated or corrected. Four approaches are addressed to obtain model-prototype similarity, to quantify scale effects and to define limiting criteria under which they can be neglected. These are inspectional analysis, dimensional analysis, calibration and scale series, which are applied to landslide generated impulse waves. Tables include both limiting criteria to avoid significant scale effects and typical scales of physical hydraulic engineering models for a wide variety of hydraulic flow phenomena. The article further shows why it is challenging to model sediment transport and distensible structures in a physical hydraulic model without significant scale effects. Possible future research directions are finally suggested.